Geographical range and impact of five biocontrol agents established on Lantana camara in South Africa - J-R. Baars; F. Heystek (BioControl, 2003)

Zinc‐bicarbonate colimitation of Emiliania huxleyi - Erik T. Buitenhuis; Klaas R. Timmermans; Hein J. W. de Baar (Limnology and Oceanography, 2003)
In analogy to the Fe hypothesis, the Zn hypothesis states that Zn may limit primary production in some regions of the world oceans and therefore influence the global carbon cycle. The proposed mechanism is via carbon limitation due to a lack of the cofactor Zn in carbonic anhydrase. In the current conceptual model for the use of inorganic carbon by E. huxleyi , carbonic anhydrase in the chloroplast generates CO 2 from HCO 3 − at the site where CO 2 is fixed by ribulose bisphosphate carboxylase oxygenase (Rubisco). The H + that is required in this reaction comes from calcification. From this it can be expected that carbonic anhydrase affects the use of HCO 3 − in photo‐synthesis. First, we grew E. huxleyi under Zn 2+ limitation. The K 1/2 for growth of E. huxleyi is 19 ± 8 pmol L −1 Zn 2+ with a minimum requirement of 9 ± 3 pmol L −1 . Additions of both ethylenediaminetetraacetic acid (EDTA) and ZnCl 2 show that EDTA is not detrimental to E. huxleyi up to a concentration of 200 µmol L −1 . Then we grew E. huxleyi under Zn 2+ ‐HCO 3 − colimitation to test the conceptual model outlined above. The results were partly inconsistent with the model. Contrary to what was expected from the conceptual model, the efficiency of CO 2 use decreased when both Zn 2+ and HCO 3 − concentrations were low, even though the experiment was conducted at a constant high concentration of CO 2 . This shows that Zn 2+ , and possibly carbonic anhydrase activity, are needed for CO 2 fixation also. In accordance with the model, we found that Zn 2+ affects the efficiency of HCO 3 − use by E. huxleyi . Since the lowest Zn 2+ concentration in the Northeast Pacific is ~0.4 pmol L −1 , Zn limitation of E. huxleyi growth may indeed occur.